Enhancing Students’ Mathematical Critical Thinking through Problem-Based Learning Assisted by MATLAB: A Classroom Action Research Study - Fanni Orlide Malau; Sondang Noverica; Anna Mariani (Pustaka Karya Mandiri, 2025)
Mathematical critical thinking is an essential competence that enables students to analyze problems, evaluate solution strategies, construct logical arguments, and make reasoned conclusions. However, students often experience difficulty in understanding abstract mathematical concepts when learning is dominated by procedural explanation and limited visual representation. This study aims to improve students’ mathematical critical thinking and learning outcomes through the implementation of Problem-Based Learning assisted by MATLAB. This classroom action research was conducted in Class VIII-B of SMP Negeri 2 Sidikalang, involving 30 students. The study was implemented in two cycles, and each cycle consisted of planning, action, observation, and reflection. Data were collected through learning outcome tests, observation of student activities, student response questionnaires, teacher interviews, and documentation. The findings show progressive improvement in students’ learning mastery and classroom engagement. In the initial condition, only 12 students, or 40%, achieved the Minimum Mastery Criteria, with a class mean score of 69.6. After Cycle I, the number increased to 18 students, or 60%, with a mean score of 75.2. After Cycle II, 27 students, or 90%, achieved mastery, with a mean score of 82.5. Observation also indicated that students became more active in analyzing problems, discussing solution strategies, using MATLAB for mathematical exploration, and presenting their reasoning. The study concludes that PBL assisted by MATLAB can support a more active, visual, collaborative, and problem-oriented mathematics learning environment.